KETAHANAN PANGAN RUMAH TANGGA NELAYAN TRADISIONAL DI KELURAHAN PASARMADANG KECAMATAN KOTAAGUNG KABUPATEN TANGGAMUS - Ferlia Devanda; Fembriarti Erry Prasmatiwi; Indah Nurmayasari (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This study aims to analyze the level of food security, factors that influence the level of food security and efforts to improve food security of fisherman households. This research is a survey conducted in coastal area Pasarmadang Village, Kotaagung Subdistrict, Tanggamus District. Respondents were 48 traditional fisherman households selected using a simple random method. Data collection was carried out in April-May 2018. The level of food security was analyzed by using cross classification between the share of food expenditure and energy adequacy, the factors that influence the level of food security were analyzed by regression of ordinal logit, and efforts to improve food security were analyzed descriptive qualitatively. The results showed that most fisherman households are in the category of food insufficiency (50.00%). The rests are in the food-resistant category (29.17%), food vulnerable (10.42%), and food insecurity (10.42%).  Factors that affect food security of fisherman households are the number of household members, education of housewives, and household income. Government efforts to improve food security include strengthening food availability, diversification and food security, utilizing yards, controlling food prices, fostering, providing facilities and infrastructure, PKH and Raskin programs. Meanwhile, efforts by fisherman households are to change diet, improve nutrition knowledge, and increase income by working outside thefishing business and employing family members.Key words: cross classification, fisherman households, food security.